UMP receives visit from Higher Education DG - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 24 February 2022 - Universiti Malaysia Pahang (UMP) received a visit from the Director General of Higher Education, Professor Dato’ Dr. Husaini Omar and a delegation from the Ministry of Higher Education at UMP Gambang Campus recently.